Ultrahigh-adhesion fine-line metal grid structure and preparation method thereof

By coating the silicon dioxide precoat, the active coating and the protective layer on the PET substrate of the metal mesh touch screen, and the blackened layer on the copper layer, the problem of insufficient copper adhesion caused by line refinement is solved, and the electrical properties and process yield of the product are improved.

CN119876873APending Publication Date: 2025-04-25牧东光电科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411980470.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing metal mesh touch screens have become thinner and thinner, resulting in relatively poor adhesion between copper and PET substrates, which are prone to abnormal phenomena such as copper wire breakage and fracture, affecting the product electrical properties and process yield.

Method used

The silicon dioxide precoat is coated on the PET substrate with a double-sided coating, a polyethyleneimine active coating is coated, and the first blackening layer, a copper layer and a second blackening layer are coated on the surface of the copper layer, and finally a polyurethane protective layer is coated to enhance the adhesion and durability of the copper layer to the PET substrate.

Benefits of technology

By increasing the surface tension of the PET substrate, enhancing the chemical bonding between the copper layer and the PET substrate, and isolating moisture and oxidizing gases, the adhesion and durability of the copper layer are significantly improved, problems such as copper wire breakage and fracture are avoided, and process yield is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876873A_ABST
    Figure CN119876873A_ABST
Patent Text Reader

Abstract

The invention discloses a fine line metal grid structure with ultrahigh adhesive force and a preparation method of the fine line metal grid structure. The fine line metal grid structure with ultrahigh adhesive force comprises a PET (Polyethylene Terephthalate) base material, a protective layer, a copper layer, an active coating and a pre-coating are sequentially adhered to the front surface of the PET base material from top to bottom; a protective layer, a copper layer, an active coating and a pre-coating are sequentially adhered to the back surface of the PET base material from bottom to top; the copper layer comprises a first blackening layer, copper and a second blackening layer which are sequentially arranged from top to bottom; the protective layer is a polyurethane coating, the active coating is a polyethyleneimine coating, and the pre-coating is a silicon dioxide coating; according to the prepared metal grid, the two faces of the PET base material are coated with the silicon dioxide pre-coating layers, the surface tension of the PET base material is improved, and the adhesive force of the copper layer is enhanced; the polyethyleneimine coating is coated to further enhance the bonding strength of the copper layer and the PET base material; and the polyurethane protection layer is coated on the surface of the copper layer, so that the durability and the stability of the copper layer are improved, the copper is prevented from being broken and damaged, and the process yield is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of touch screens, and in particular to a fine-line metal grid structure with ultra-high adhesion and a preparation method thereof. Background Art

[0002] Conventional Metal Mesh touch screens are mainly made of raw copper materials, which are processed through processes such as photoresist coating, exposure, development, etching, and film stripping to produce edge routing with a certain line width and line spacing and an in-plane metal mesh pattern with a certain Mesh line width. With the upgrading of product technology and the market demand for ultra-thin and ultra-narrow bezel products, the industry has higher and higher requirements for the edge routing of metal meshes and the Mesh lines of in-plane metal meshes. The line width and line spacing of edge routings have been gradually reduced from 15um / 15um to 6um / 6um, and the Mesh line width of in-plane metal meshes has been reduced from 3.5um~5.5um to 1um~2um. The thinner the line, the higher the requirement.

[0003] The structure of the existing metal grid is as follows Figure 1 As shown, it is composed of a front copper layer 10, a PET substrate 1, and a back copper layer 11. The PET substrate 1 is blackened on both sides, copper is plated on the surface of the blackened layer, and then the copper surface is blackened. Since the thickness of the blackened layer is relatively thinner than the thickness of the copper layer, the three layers of blackened layer-copper-blackened layer on the front and back of the PET can be simply collectively referred to as the copper layer, that is, the adhesion between the copper and the blackened layer, and the adhesion between the blackened layer and the PET can be considered as the adhesion between the copper and the PET substrate. The adhesion between the copper and the PET substrate will be relatively poor as the line is thinner, and it is more likely to cause abnormal phenomena such as copper breakage and folding, which will affect the electrical properties of the product and reduce the process yield. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a fine-line metal grid structure with ultra-high adhesion and a preparation method thereof, wherein the copper is not easily broken or damaged, the product has good electrical properties and a high yield.

[0005] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a fine-line metal grid structure with ultra-high adhesion, comprising a PET substrate; the front side of the PET substrate is sequentially provided with a protective layer, a copper layer, an active coating layer and a pre-coating layer from top to bottom; the back side of the PET substrate is sequentially provided with a protective layer, a copper layer, an active coating layer and a pre-coating layer from bottom to top.

[0006] In one embodiment, the copper layer includes a first blackened layer, copper, and a second blackened layer which are sequentially arranged up and down.

[0007] In one embodiment, the protective layer is a polyurethane coating, the active coating is a polyethyleneimine coating, and the pre-coating is a silicon dioxide coating.

[0008] A method for preparing a fine-line metal grid structure with ultra-high adhesion comprises the following steps:

[0009] S1. Copper coating is applied on the front and back of the PET substrate using magnetron sputtering technology:

[0010] S2, spin coating the active coating on the pre-coating on the front and back sides of the PET substrate;

[0011] S2, coating the active coating on the front and back of the PET substrate with a first blackened layer by a magnetron sputtering process;

[0012] S4, coating the first blackened layer on the front and back sides of the PET substrate with a copper layer by using a magnetron sputtering process;

[0013] S5, coating a second blackening layer on the copper layer surface on the front and back sides of the PET substrate by using a magnetron sputtering process;

[0014] S6. Spin-coat a protective layer on the second blackened layer on the front and back sides of the PET substrate to prepare a metal grid structure.

[0015] In one embodiment, in step S1, when the pre-coating layer is silicon dioxide, the method for preparing the silicon dioxide coating layer comprises the following steps:

[0016] S1a, removing impurities from the surface of the PET substrate, setting the substrate temperature to 40°C;

[0017] S1b, reduce the system vacuum to below 6*10-4Pa, introduce a mixed gas of argon with a flow rate of 0sccm to 30sccm and oxygen with a flow rate of 2sccm to 10sccm, and stabilize the working pressure to 0.25Pa;

[0018] S1c, set the system RF power to 150 W, the sputtering rate to 0.2 nm / s, the sputtering time to 100 s, set the distance between the target and the PET substrate to 60 mm, and then magnetron sputter a 30 nm thick silicon dioxide coating.

[0019] In one embodiment, in step S2, when the active coating is a polyethyleneimine coating, the method for preparing the polyethyleneimine coating comprises the following steps:

[0020] S2a, adding dilute hydrochloric acid or ammonia water to a 0.5 wt% polyethyleneimine solution to adjust the pH value to 6-7;

[0021] S2b, adding 10% by mass of glutaraldehyde crosslinking agent and 0.01% to 0.05% of sodium dodecyl sulfate surfactant to prepare a spin coating solution;

[0022] S2c, a 30 nm active layer was coated on the front and back of the PET coated with a pre-coating at a rotation speed of 3000 rpm and a spin coating time of 45 s. After coating, the polyethyleneimine coating was prepared by curing at 70° C. for 10 min.

[0023] In one embodiment, in step S3, the method for preparing the first blackened layer includes the following steps:

[0024] S3a, reduce the vacuum degree to 5x 10-4Pa ~ 6x 10-4Pa, select high purity> 99.99% copper oxide target material, introduce argon oxygen-argon mixed gas, and the working pressure range of sputtering gas is 0.3Pa ~ 0.6Pa;

[0025] S3b, set the system RF power to 50W-150W, the sputtering rate to 0.3nm / s-0.5nm / s, the sputtering time to 100s-333s, set the distance between the copper oxide target and the surface of the PET substrate to 10cm-15cm, and then magnetron sputter out a first blackening layer of 50nm-100nm.

[0026] In one embodiment, in step S4, the method for preparing the copper layer comprises the following steps:

[0027] S4a, reduce the system vacuum to 5x 10-4Pa~6x 10-4Pa, select copper target with high purity>99.99% as target, introduce argon with high purity>99.99%, and the working pressure range of sputtering gas is 0.2Pa~0.5Pa;

[0028] S4b, set the system RF power to 100W-200W, the sputtering rate to 1nm / s-2nm / s, the sputtering time to 200s-600s, set the distance between the copper target and the surface of the PET substrate to 10cm-15cm, and then magnetron sputter out a copper layer with a thickness of 400nm-600nm.

[0029] In one embodiment, in step S5, the preparation method of the second blackened layer is the same as the preparation method of the first blackened layer.

[0030] In one embodiment, in step S6, when the protective layer is a polyurethane coating, the method for preparing the polyurethane coating comprises the following steps:

[0031] S6a, adding 0.01% to 0.05% sodium dodecyl sulfate surfactant to a 2wt% polyethyleneimine solution to prepare a spin coating solution;

[0032] S6b, a 30 nm protective layer was coated on the copper layer surface on the front and back sides of the PET substrate at a rotation speed of 2500 rpm and a spin coating time of 40 s. After coating, the protective layer was cured at 80° C. for 15 min to prepare a polyurethane coating.

[0033] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0034] The invention discloses a fine-line metal grid structure with ultra-high adhesion and a preparation method thereof. In the prepared metal grid structure, a layer of silicon dioxide pre-coating layer is plated on both sides of a PET substrate to increase the surface tension of the PET substrate and enhance the adhesion of the copper layer; an organic polymer active coating is applied to further enhance the bonding strength between the copper layer and the PET substrate through chemical bonding; a polyurethane protective layer is applied on the surface of the copper layer to isolate moisture and oxidizing gases, thereby enhancing the durability and stability of the copper layer, thereby avoiding abnormal phenomena such as copper wire breakage and folding, and improving the process yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The technical solution of the present invention is further described below in conjunction with the accompanying drawings:

[0036] Figure 1 It is a structural schematic diagram of a metal grid structure in the prior art;

[0037] Figure 2 A schematic structural diagram of a metal mesh structure in one embodiment of the present invention;

[0038] Figure 3 This is a schematic diagram of the structure of a copper layer in one embodiment of the present invention;

[0039] Figure 4 A schematic diagram of the preparation process of a metal mesh in one embodiment of the present invention;

[0040] Among them: 1. PET substrate; 2. protective layer; 3. copper layer; 4. active coating; 5. pre-coating layer; 10. upper copper layer; 11. lower copper layer; 30. copper; 31. first blackening layer; 32. second blackening layer. DETAILED DESCRIPTION

[0041] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present application.

[0042] The present invention provides a thin-line metal grid structure with ultra-high adhesion and a preparation method thereof, so as to solve the problem in the prior art that as the lines become thinner and thinner, the adhesion between copper and a PET substrate becomes relatively poorer, copper wire breakage, bends and other abnormal phenomena are more likely to occur, and the process yield is low.

[0043] For ease of understanding, the specific process in the embodiments of the present application is described below. Figures 2 to 3 A fine-line metal grid structure with ultra-high adhesion in an embodiment of the present application includes a PET substrate 1, and a protective layer 2, a copper layer 3, an active coating 4 and a pre-coating layer 5 are sequentially attached to the front side of the PET substrate 1 from top to bottom; a protective layer 2, a copper layer 3, an active coating 4 and a pre-coating layer 5 are sequentially attached to the back side of the PET substrate 1 from bottom to top.

[0044] Furthermore, the copper layer 3 includes a first blackened layer 31 , copper 30 , and a second blackened layer 32 , and the first blackened layer 31 and the second blackened layer 32 are relatively thin.

[0045] Furthermore, in this embodiment, the PET substrate is a transparent flexible material with a thickness of 25um to 125um, and a commonly used thickness of 50um, and mainly plays the role of bearing the copper layer and the plating layer.

[0046] Furthermore, the pre-coating layer 5 is a 20 nm thick silica coating coated on the front and back sides of the PET substrate 1 by a magnetron sputtering process. On the one hand, the silica coating can protect the PET substrate and prevent small molecular particles inside the PET substrate from migrating to the surface of the PET substrate due to Brownian motion, affecting the cleanliness of the surface of the PET substrate, thereby reducing the surface tension of the PET substrate and weakening the adhesion between the copper layer and the PET substrate; on the other hand, the evenly distributed silica coating can increase the surface tension of the PET substrate 1, increase the contact area between the copper layer 3 and the surface of the PET substrate 1, and enhance the adhesion of the copper layer 3 by physical bonding.

[0047] Secondly, if the thickness of silicon dioxide is too thick or too thin, the adhesion of the copper layer will be reduced. Generally, the thickness of silicon dioxide is between 10nm and 50nm. The adhesion of the copper layer is best when the thickness is 20nm. When the thickness of silicon dioxide is less than 10nm, silicon dioxide is not enough to form a relatively uniform coating on the surface of the PET substrate, affecting the adhesion of the copper layer; when the thickness of silicon dioxide is greater than 50nm, the power required for coating is large, which will cause greater stress inside the silicon dioxide, thereby affecting the uniformity and adhesion of the silicon dioxide coating, and further reducing the adhesion of the copper layer; the optimal thickness of silicon dioxide is 20nm, which can both increase the surface tension of the PET substrate and ensure the uniformity of the silicon dioxide coating.

[0048] Furthermore, the active coating 4 is a polyethyleneimine organic polymer coating applied on the upper surface of the pre-coating 5 on the front side of the PET substrate 1 or the lower surface of the pre-coating 5 on the back side by a spin coating process.

[0049] In addition, adding 10% of glutaraldehyde crosslinker to polyethyleneimine by mass can enhance the chemical bonding force of the PET surface and further improve the surface activity of the active coating; adding a very small amount of sodium dodecyl sulfate surfactant can improve the spreadability of polyethyleneimine on the PET surface, enhance the leveling performance of polyethyleneimine, and improve the thickness uniformity of the active coating.

[0050] The polyethyleneimine organic polymer coating uses chemical bonds to make the copper layer adhere to the surface of the organic polymer coating better, further enhancing the adhesion between the copper layer 3 and the PET substrate. The coating process must ensure the uniformity of the coating and avoid the generation of coating bubbles. The general coating thickness is between 5nm and 50nm, which is adjusted according to specific equipment and process parameters.

[0051] In addition, if the active coating 4 is too thick, it will easily cause internal stress in the copper layer, causing slight deformation of the copper material to produce ripples; if the active coating 4 is too thin, it will easily fail to improve the surface activity of the active coating, resulting in weakened bonding between the copper layer and the active coating. The recommended optimal thickness of the active coating 4 is 30nm.

[0052] For the spraying of the active coating 4, the spin coating process for coating polyethyleneimine has better uniformity than other dipping or spraying processes.

[0053] Furthermore, the copper layer 3 is a copper layer of a three-layer structure of a first black layer-copper-second black layer, which is continuously coated on the surface of the active coating 4 by a magnetron sputtering process, wherein the thickness of the first black layer 31 and the second black layer 32 is 50nm-100nm, and the thickness of copper is 400nm-600nm. The first black layer and the second black layer mainly play the role of shielding the color of copper and adjusting the overall visual effect of the metal grid; copper mainly plays the role of conductivity and is the core element of the touch screen with capacitance characteristics. The time and temperature of vacuum evaporation have an important influence on the thickness, square resistance, uniformity and adhesion of the copper layer. A higher temperature is conducive to the copper layer adhering to the PET substrate.

[0054] Furthermore, the protective layer 2 is a polyurethane coating applied on the surface of the copper layer 3 by a spin coating process. A very small amount of sodium dodecyl sulfate surfactant can be added to the polyurethane solution to improve the spreadability of the polyurethane solution on the PET surface, enhance the leveling performance of the polyurethane, and improve the thickness uniformity of the protective layer; it can also be applied multiple times to make the polyurethane thickness uniform, but each coating needs to be cured before the second coating can be performed. After curing, the polyurethane coating will be evenly distributed on the surface of the copper layer, protecting the copper layer from corrosion in oxidation, humidity, and stress environments, preventing the copper layer and the PET substrate from falling off or stratifying, improving the durability and stability of the copper layer, and enhancing the adhesion between the copper layer and the PET.

[0055] Generally, the thickness of protective layer 2 is between 20nm and 2um. The thickness is adjusted according to the specific product application. It is recommended to apply 2um to the surface that is directly exposed to the external environment for a long time, and to apply less than 100nm to the surface that is used indoors and not directly exposed to the external environment. If the protective layer 2 is too thick, it is easy to cause internal stress in the copper layer, causing slight deformation of the copper material to produce ripples; if the protective layer 2 is too thin, it is easy to be unable to isolate the external moisture and oxygen and other oxidizing gases, causing the copper layer to be oxidized, thereby weakening the bonding force between the copper layer and the active coating, and also reducing the adhesion between the copper layer and the PET substrate. The recommended optimal value of the polyurethane coating thickness is 30nm.

[0056] In summary, the ultra-high adhesion fine-line metal grid of the present invention is coated with a layer of silicon dioxide pre-coating on both sides of the PET substrate to increase the surface tension of the PET substrate and enhance the adhesion of the copper layer; an organic polymer active coating is applied to further enhance the bonding strength between the copper layer and the PET substrate through chemical bonding; a polyurethane protective layer is coated on the surface of the copper layer to isolate moisture and oxidizing gases, thereby improving the durability and stability of the copper layer, thereby avoiding abnormal phenomena such as copper wire breakage and folding, and improving the process yield.

[0057] See also Figure 4 The present invention also discloses a method for preparing a metal grid, which comprises the following steps:

[0058] S1, using magnetron sputtering process to coat the front and back of the PET substrate with a pre-coating layer;

[0059] In step S1, when the pre-coating layer is silicon dioxide, the method for preparing the silicon dioxide coating layer comprises the following steps:

[0060] S1a, use plasma or plasma to treat both sides of the PET substrate to remove pollutants, impurities, foreign matter, etc. on the surface of the PET substrate, and set the substrate temperature range to 30°C to 60°C. If the substrate temperature is too high, it is easy to cause deformation of the PET substrate and affect the adhesion of the copper layer. In this embodiment, the substrate temperature is 40°C;

[0061] S1b, reduce the system vacuum to below 6*10-4Pa, introduce a mixed gas of argon with a flow rate of 0sccm to 30sccm and oxygen with a flow rate of 2sccm to 10sccm, and stabilize the working pressure to 0.25Pa, wherein the mixed gas of argon and oxygen is more conducive to the production of silicon dioxide coatings with precise stoichiometric ratio;

[0062] S1c, set the system RF power to 150W, the sputtering rate to 0.2nm / s, the sputtering time to 100s, set the distance between the target and the PET substrate to 60mm, and then magnetron sputter out a 30nm thick silicon dioxide coating. This silicon dioxide coating has uniform thickness, good density and high surface tension.

[0063] S2, spin coating the active coating on the pre-coating on the front and back sides of the PET substrate;

[0064] In step S2, when the active coating is a polyethyleneimine coating, the method for preparing the polyethyleneimine coating comprises the following steps:

[0065] S2a, adding dilute hydrochloric acid or ammonia water to a 0.5 wt% polyethyleneimine solution to adjust the pH value to 6-7;

[0066] S2b, adding 10% by mass of glutaraldehyde crosslinking agent and 0.01% to 0.05% of sodium dodecyl sulfate surfactant to prepare a spin coating solution;

[0067] S2c, a 30 nm active layer was coated on the front and back of the PET coated with a pre-coating at a rotation speed of 3000 rpm and a spin coating time of 45 s. After coating, the polyethyleneimine coating was prepared by curing at 70° C. for 10 min.

[0068] In this step, the polyethyleneimine solution uses pure water or ethanol or a mixture of pure water and ethanol as a solvent, and its concentration range is adjusted between 0.1%wt and 2.5wt%. The commonly used surface modification concentration is 0.5wt%. The pH value of the solution is adjusted with dilute hydrochloric acid or ammonia water to stabilize the pH value at 6 to 7 to enhance the stability of the solution. At the same time, a glutaraldehyde cross-linking agent is added at a mass ratio of 10% relative to the polyethyleneimine and a very small amount of sodium dodecyl sulfate surfactant is added at a concentration of 0.01% to 0.05% to further improve the surface activity and spreadability of the active coating.

[0069] In addition, after the spin coating is completed, the film-forming active coating is cured, generally by oven heat baking or IR line baking, the baking conditions are 60℃~90℃, the baking time is 10min~15min, and the recommended optimal baking temperature for coating 30nm thick polyethyleneimine is 70℃, and the baking time is 10min. This is beneficial to enhance the bonding ability between the copper layer and the pre-coating layer through chemical bonding, and improve the adhesion between the copper and the PET substrate.

[0070] S3, coating the active coating on the front and back of the PET substrate with a first blackened layer by a magnetron sputtering process;

[0071] S4, coating the first blackened layer on the front and back sides of the PET substrate with a copper layer by using a magnetron sputtering process;

[0072] S5, coating a second blackening layer on the copper layer surface on the front and back sides of the PET substrate by using a magnetron sputtering process;

[0073] In step S3 to step S5, the preparation methods of the first blackened layer and the second blackened layer are the same, except that the two are located on the upper surface and the lower surface of the copper, respectively.

[0074] The following is a description of the preparation direction of the first blackened layer. The preparation method of the first blackened layer is as follows:

[0075] S3a, reduce the vacuum degree to 5x 10-4Pa ~ 6x 10-4Pa, select high purity> 99.99% copper oxide target material, introduce argon oxygen-argon mixed gas, and the working pressure range of sputtering gas is 0.3Pa ~ 0.6Pa;

[0076] S3b, set the system RF power to 50W ~ 150W, the sputtering rate to 0.3nm / s ~ 0.5nm / s, the sputtering time to 100s ~ 333s, set the distance between the copper oxide target and the surface of the PET substrate to 10cm ~ 15cm, and then magnetron sputter out a first blackened layer with a uniform thickness of 50nm ~ 100nm and good density.

[0077] Furthermore, in step S4, the method for preparing the copper layer includes the following steps:

[0078] S4a, reduce the system vacuum to 5x 10-4Pa~6x 10-4Pa, select copper target with high purity>99.99% as target, introduce argon with high purity>99.99%, and the working pressure range of sputtering gas is 0.2Pa~0.5Pa;

[0079] S4b, set the system RF power to 100W-200W, sputtering rate to 1nm / s-2nm / s, sputtering time to 200s-600s, set the distance between the copper target and the surface of the PET substrate to 10cm-15cm, and then magnetron sputter out a copper layer with a uniform thickness of 400nm-600nm and good density. This is conducive to increasing the contact area between the copper layer and the PET substrate, increasing the physical bonding ability between the copper layer and the PET substrate, and improving the adhesion between the copper and the PET substrate.

[0080] S6. Spin-coat a protective layer on the second blackened layer on the front and back sides of the PET substrate to prepare a metal grid structure.

[0081] In step S6, when the protective layer is a polyurethane coating, the method for preparing the polyurethane coating comprises the following steps:

[0082] S6a, adding 0.01% to 0.05% sodium dodecyl sulfate surfactant to a 2wt% polyethyleneimine solution to prepare a spin coating solution;

[0083] S6b, a 30 nm protective layer was coated on the copper layer surface on the front and back sides of the PET substrate at a rotation speed of 2500 rpm and a spin coating time of 40 s. After coating, the protective layer was cured at 80° C. for 15 min to prepare a polyurethane coating.

[0084] The curing steps are as follows: Generally, oven heat baking or IR line baking is adopted, the baking conditions are 60℃~100℃, the baking time is 10min~20min, and the recommended optimal baking temperature for coating 30nm thick polyurethane is 80℃, and the baking time is 15min. Under the above process parameters, a polyurethane coating with uniform thickness and excellent surface isolation performance can be spin-coated to prevent the copper layer from being oxidized and corroded by external moisture, oxygen and other oxidizing gases, avoid the copper layer from falling off, and improve the adhesion between the copper layer and the PET substrate.

[0085] As described above, the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.

Claims

1. A fine-line metal grid structure with ultra-high adhesion, characterized in that: The invention comprises a PET substrate; a protective layer, a copper layer, an active coating layer and a pre-coating layer are sequentially attached to the front side of the PET substrate from top to bottom; and a protective layer, a copper layer, an active coating layer and a pre-coating layer are sequentially attached to the back side of the PET substrate from bottom to top.

2. The ultra-high adhesion fine line metal grid structure according to claim 1, characterized in that: The copper layer includes a first blackened layer, copper and a second blackened layer which are sequentially arranged up and down.

3. The ultra-high adhesion fine line metal grid structure according to claim 1, characterized in that: The protective layer is a polyurethane coating, the active coating is a polyethyleneimine coating, and the pre-coating is a silicon dioxide coating.

4. The method for preparing a fine-line metal grid structure with ultra-high adhesion according to claim 2, characterized in that: The steps include: S1. Copper coating is applied on the front and back of the PET substrate using magnetron sputtering technology: S2, spin coating the active coating on the pre-coating on the front and back sides of the PET substrate; S2, coating the active coating on the front and back of the PET substrate with a first blackened layer by a magnetron sputtering process; S4, coating the first blackened layer on the front and back sides of the PET substrate with a copper layer by using a magnetron sputtering process; S5, coating a second blackening layer on the copper layer surface on the front and back sides of the PET substrate by using a magnetron sputtering process; S6. Spin-coat a protective layer on the second blackened layer on the front and back sides of the PET substrate to prepare a metal grid structure.

5. The method for preparing a fine-line metal grid structure with ultra-high adhesion according to claim 4, characterized in that: The method comprises the following steps: In step S1, when the pre-coating layer is silicon dioxide, the method for preparing the silicon dioxide coating layer comprises the following steps: S1a, removing impurities from the surface of the PET substrate, setting the substrate temperature to 40°C; S1b, reduce the system vacuum to below 6*10-4Pa, introduce a mixed gas of argon with a flow rate of 0sccm to 30sccm and oxygen with a flow rate of 2sccm to 10sccm, and stabilize the working pressure to 0.25Pa; S1c, set the system RF power to 150 W, the sputtering rate to 0.2 nm / s, the sputtering time to 100 s, set the distance between the target and the PET substrate to 60 mm, and then magnetron sputter a 30 nm thick silicon dioxide coating.

6. The method for preparing a fine-line metal grid structure with ultra-high adhesion according to claim 4, characterized in that: In step S2, when the active coating is a polyethyleneimine coating, the method for preparing the polyethyleneimine coating comprises the following steps: S2a, adding dilute hydrochloric acid or ammonia water to a 0.5 wt% polyethyleneimine solution to adjust the pH value to 6-7; S2b, adding 10% by mass of glutaraldehyde crosslinking agent and 0.01% to 0.05% of sodium dodecyl sulfate surfactant to prepare a spin coating solution; S2c, a 30 nm active layer was coated on the front and back of the PET coated with a pre-coating at a rotation speed of 3000 rpm and a spin coating time of 45 s. After coating, the polyethyleneimine coating was prepared by curing at 70° C. for 10 min.

7. The method for preparing a fine-line metal grid structure with ultra-high adhesion according to claim 4, characterized in that: In step S3, the method for preparing the first blackened layer includes the following steps: S3a, reduce the vacuum degree to 5x 10-4Pa ~ 6x 10-4Pa, select high purity> 99.99% copper oxide target material, introduce argon oxygen-argon mixed gas, and the working pressure range of sputtering gas is 0.3Pa ~ 0.6Pa; S3b, set the system RF power to 50W-150W, the sputtering rate to 0.3nm / s-0.5nm / s, the sputtering time to 100s-333s, set the distance between the copper oxide target and the surface of the PET substrate to 10cm-15cm, and then magnetron sputter out a first blackening layer of 50nm-100nm.

8. The method for preparing a fine-line metal grid structure with ultra-high adhesion according to claim 4, characterized in that: In step S4, the method for preparing the copper layer comprises the following steps: S4a, reduce the system vacuum to 5x 10-4Pa~6x 10-4Pa, select copper target with high purity>99.99% as target, introduce argon with high purity>99.99%, and the working pressure range of sputtering gas is 0.2Pa~0.5Pa; S4b, set the system RF power to 100W-200W, the sputtering rate to 1nm / s-2nm / s, the sputtering time to 200s-600s, set the distance between the copper target and the surface of the PET substrate to 10cm-15cm, and then magnetron sputter out a copper layer with a thickness of 400nm-600nm.

9. The method for preparing a fine-line metal grid structure with ultra-high adhesion according to claim 7, characterized in that: In step S5, the preparation method of the second blackened layer is the same as the preparation method of the first blackened layer.

10. The method for preparing a fine-line metal grid structure with ultra-high adhesion according to claim 4, characterized in that: In step S6, when the protective layer is a polyurethane coating, the method for preparing the polyurethane coating comprises the following steps: S6a, adding 0.01% to 0.05% sodium dodecyl sulfate surfactant to a 2wt% polyethyleneimine solution to prepare a spin coating solution; S6b, a 30 nm protective layer was coated on the copper layer surface on the front and back sides of the PET substrate at a rotation speed of 2500 rpm and a spin coating time of 40 s. After coating, the protective layer was cured at 80° C. for 15 min to prepare a polyurethane coating.